Household preparedness for natural disasters : a review of literature - Kitanović, Jelena (Array, 2020)
Numerous literature reviews have been carried out in the area of household preparedness activities for natural disasters. The present study aims to summarize the latest findings of natural disaster preparedness levels and aims to address the following research questions: What evidence is there for natural disaster preparedness levels? What are the demographic characteristics and potential variables that influence natural disaster preparedness? What has been reported in major bibliographic databases? The first step involved a systematic search to identify relevant studies published between 1995 and 2019 in the following electronic databases EBSCOhost, Scopus, ScienceDirect, and Web of Science. Nineteen studies met the inclusion criteria and were included in the final review. By analysing the available literature, it has been observed that the in the area of preparedness activities for natural disasters most households do not have a rapid development plan for preparation. Although little research has been done on the preparedness of the older population, it will be necessary to analyse which communication methods would be used in case of a natural disaster, as well as look into the benefits of their use for networking and rapid communication of information before and during the natural disaster.